Answer: The correct option is (B) [tex]2y^2-y-6=0.[/tex]
Step-by-step explanation: We are given the following system of equations :
[tex]x=y^2-1~~~~~~~~~~~~~~~~~~~~~~~~~~(i)\\\\2x-y=4~~~~~~~~~~~~~~~~~~~~~~~~~~(ii)[/tex]
We are to find the equation that could be the result of using substitution to solve the above system.
Substituting the value of x from equation (i) in equation (ii), we get
[tex]2x-y=4\\\\\Rightarrow 2(y^2-1)-y=4\\\\\Rightarrow 2y^2-2-y=4\\\\\Rightarrow 2y^2-y-2-4=0\\\\\Rightarrow 2y^2-y-6=0.[/tex]
Thus, the required equation is [tex]2y^2-y-6=0.[/tex]
Option (B) is CORRECT.